Discourse representation on Indonesian socio-political situation in the Instagram posts of an English-speaking Indonesian community - Monika Dewanty; Barli Bram (Universitas Negeri Yogyakarta, 2023)
This study aims to explore the discourse representation that is used in the Instagram posts of an unofficial news account for the English-speaking Indonesian community. The studies about discourse representation are mostly done in a formal setting and comparative setting. Hence, this study intends to show the discourse representation that is used in an unofficial news account that focuses on the Indonesian socio-political situation. This study used qualitative research to collect and analyze the data. The data was taken from 50 Instagram posts. The data were analyzed by identifying the sentences based on the discourse representation theory. The finding shows that both in direct and indirect discourse, the reporting verbs are mostly used. The reporting verbs in the direct discourse is 69% and indirect discourse 78%. Meanwhile, indirect discourse is the mode and form of discourse representation that is mostly used in Instagram posts with a percentage of 82%.